KSZTAŁTOWANIE KOMPETENCJI KOMUNIKACYJNEJ W KLASIE JĘZYKA OBCEGO. PERSPEKTYWA UCZNIA - Sowa, Magdalena (Neofilolog, 2019)
This article attempts to evaluate the quality and effectiveness of foreign language teaching in Polish schools by giving learners’ views on the process of the teaching of languages. The opinions presented come from a questionnaire carried out among pupils who learn various languages. The results of the survey are intended to show the learning situation as seen by students themselves. Their description and assessment of school learning enable us, to judge whether being taught a language in school satisfies their needs and expectations, and also to assess whether and to what extent this learning is consistent with European language policy.